Penetapan Kadar Hidrokuinon pada Krim Pemutih Wajah yang Beredar di Pasar 45 Kota Manado dengan Metode Spektrofotometri UV-VIS - Rosadalima Mere Tuku; Rifani Hutami Supardi; Ahlan Sangkal (STIKes Ibnu Sina Ajibarang, 2025)
Long-term use of hydroquinone compounds can reduce melanin production, causing the skin to lose its protective function against sunlight. Manufacturers promote products in various media to increase sales, in fact the prevalence of illegal cosmetics is increasing every year. The purpose of this study was to determine the levels of hydroquinone contained in various brands of facial whitening cream cosmetics circulating in the 45 Manado City markets. Quantitative testing using the UV-Vis spectrophotometry method. The results showed that 5 samples taken in the 45 Manado City markets contained hydroquinone with sample levels of (A) 0,0339% and (B) 0,0536%. So it can be concluded that 2 samples of facial whitening cream do not comply with BPOM Regulation Number 23 of 2019 concerning facial whitening cream cosmetic preparations.